Carotid occlusion: Impact of cerebral hemodynamic impairment on cognitive performances. (11th September 2020) - Viticchi, Giovanna; Falsetti, Lorenzo; Buratti, Laura; Acciarri, Maria C.; Emiliani, Andrea; Bartolini, Marco; Silvestrini, Mauro
Abstract : Objectives: The aim of this study was to investigate whether the presence of carotid artery occlusion (CO) may be associated with different cognitive performances in relation to the side of the occlusion and its hemodynamic consequences. Methods: During a 12‐month period, 61 asymptomatic patients, 32 with right and 29 with left CO, were enrolled. Each patient underwent an assessment of cerebrovascular reactivity (CVR) to hypercapnia with transcranial Doppler (TCD) ultrasonography using the breath‐holding index (BHI). Neuropsychological assessment evaluating performances of the hemisphere ipsilateral to CO were administered at entry (T0 ) and then repeated after 2 years (T1 ). Results: Scores obtained at colored progressive matrices (CPM) and Rey Complex Figure Copy Test were significantly lower at T0 in patients with reduced BHI values ipsilateral to CO. Multivariate models showed that reduced BHI values were also associated to a significant decrease from T0 to T1 in scores obtained for CPM and Categorical Verbal Fluency tests, respectively, in patients with right ( P = 0.002) or left CO ( P = 0.004). Conclusions: These findings suggest that hemodynamic alterations could be involved in the reduction in cognitive function regulated by the hemisphere ipsilateral to CO. The assessment of CVR with TCD ultrasonography may be a reliable approach for the individuation of asymptomatic patients with CO at increased risk of cognitive deterioration.